Trade Credit and Informational Asymmetry - SMITH, JANET KIHOLM (Journal of Finance, 1987)
ABSTRACT Commonly used trade credit terms implicitly define a high interest rate that operates as an efficient screening device where information about buyer default risk is asymmetrically held. By offering trade credit, a seller can identify prospective defaults more quickly than if financial institutions were the sole providers of short‐term financing. The information is valuable in cases where the seller has made nonsalvageable investments in buyers since it enables the seller to take actions to protect such investments.